Improving winter condition simulations in SURFEX-TEB v9.0 with a multi-layer snow model and ice - G. Colas; V. Masson; F. Bouttier; L. Bouilloud; L. Pavan; V. Karsisto (Geoscientific Model Development)
In winter, snow- and ice-covered artificial surfaces are important aspects of the urban climate and trigger road maintenance operations. Urban climate and road weather models have specialized in simulating these conditions in cities or in the countryside, respectively. In this study, we intend to bridge the gap between road weather models and urban climate models in terms of cold region urban modelling and artificial surface condition predictions in any environment. We have refined the modelling of road surface processes related to winter conditions in the Town Energy Balance (TEB), an urban climate model designed for complex environments. We have developed an ice content prediction to account for the freezing and melting of the water content on the surface. Additionally, we have enhanced the TEB representation of snow on road, moving from a single-layer snow model (1-L), to a more precise multi-layer snow model known as Explicit Snow (ES). We have isolated the winter surface processes from other physical interactions by limiting the evaluation of the experiments to open environments. The experiments are carried out at two locations: the Col de Porte in the Alps and a road weather station in southern Finland. Our findings show that the enhanced TEB model (named TEB-ES) outperforms TEB, as well as a benchmark model, ISBA-Route/CROCUS, but with mixed results against a multiple linear regression in-sample algorithm. For roads with high traffic and/or winter maintenance operations, future modelling work should focus on the representation of anthropic effects.